2018
DOI: 10.1590/1984-0462/;2018;36;1;00015
|View full text |Cite
|
Sign up to set email alerts
|

Associação Entre a Fração Exalada De Óxido Nítrico E Dados Da Espirometria E O Controle Clínico Da Asma Em Crianças E Adolescentes

Abstract: Objective: To evaluate the association between fraction of exhaled nitric oxide (FeNO) values and forced expiratory volume in the first second (FEV1) and the level of asthma control, as proposed by the Global Initiative for Asthma (GINA), in asthmatic children and adolescents attended at the National Institute of Women, Children and Adolescents Health Fernandes Figueira of Fundação Oswaldo Cruz (IFF/FIOCRUZ).Methods: This was a cross-sectional study, with a review of medical records of 90 asthmatics between 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The reported prevalence, based on airflow obstruction, ranges from 23.5% to 60% in pediatric asthma. 6 , 10 , 11 , 15 Lo et al 10 studied 575 children with asthma treated in the United Kingdom and found that 23.5% had airflow obstruction. Another recent prospective study 15 reported that 27.5% of Thai children with well-controlled asthma still had airflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported prevalence, based on airflow obstruction, ranges from 23.5% to 60% in pediatric asthma. 6 , 10 , 11 , 15 Lo et al 10 studied 575 children with asthma treated in the United Kingdom and found that 23.5% had airflow obstruction. Another recent prospective study 15 reported that 27.5% of Thai children with well-controlled asthma still had airflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 However, many controversial issues remain regarding the use of lung function to classify asthma severity or predict future asthma outcomes in pediatric asthma studies. Data from 416 children in a controlled clinical trial 6 showed a significant association between pre-bronchodilator FEV1 and asthma outcomes. The lower the FEV1 percentage, the higher the risk of asthma exacerbation in the following 4 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation